2014
DOI: 10.1088/0004-637x/782/2/69
|View full text |Cite
|
Sign up to set email alerts
|

The Coevolution of Supermassive Black Holes and Massive Galaxies at High Redshift

Abstract: We exploit the recent, wide samples of far-infrared (FIR) selected galaxies followed-up in X rays and of X-ray/optically selected active galactic nuclei (AGNs) followed-up in the FIR band, along with the classic data on AGN and stellar luminosity functions at high redshift z 1.5, to probe different stages in the coevolution of supermassive black holes (BHs) and host galaxies. The results of our analysis indicate the following scenario: (i) the star formation in the host galaxy proceeds within a heavily dust-en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 312 publications
(516 reference statements)
15
115
0
Order By: Relevance
“…Such a scenario is identical to that advocated by Gruppioni et al (2013) for the population most resembling the ULIRGs we consider here, in which the number counts of various types of Herschel sources across four fields were used, along with a variety of other evidence, to deduce the evolutionary scenario for galaxies with powerful coeval starburst and AGN activity. It is also similar to the model adopted to fit a compilation of Herschel observations of X-ray AGN hosts in Lapi et al (2014). The above scenario does not preclude the possibility of additional quenching occuring due to processes associated with the star formation itself (see, e.g., Cen 2012), processes which can be quite strong in galaxies with the typical SFRs of the ULIRGs in the full SPIRE sample.…”
Section: The Role Of Agn In Starbursting Galaxiessupporting
confidence: 58%
See 3 more Smart Citations
“…Such a scenario is identical to that advocated by Gruppioni et al (2013) for the population most resembling the ULIRGs we consider here, in which the number counts of various types of Herschel sources across four fields were used, along with a variety of other evidence, to deduce the evolutionary scenario for galaxies with powerful coeval starburst and AGN activity. It is also similar to the model adopted to fit a compilation of Herschel observations of X-ray AGN hosts in Lapi et al (2014). The above scenario does not preclude the possibility of additional quenching occuring due to processes associated with the star formation itself (see, e.g., Cen 2012), processes which can be quite strong in galaxies with the typical SFRs of the ULIRGs in the full SPIRE sample.…”
Section: The Role Of Agn In Starbursting Galaxiessupporting
confidence: 58%
“…This is not the first time this trend has been observed. In two different studies covering different fields, Kartaltepe et al (2010a) and Juneau et al (2013;hereafter J13) observed that the fraction of galaxies which host AGN, AGN selected by a wide variety of methods, was a strong function of L TIR (see also the review of this trend for galaxies hosting X-ray AGN in Lapi et al 2014). These samples were, however, selected at shorter wavelengths, meaning that the contamination to L TIR from the AGN was more problematic than it is in a SPIRE-selected sample.…”
Section: The Role Of Agn In Starbursting Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is possible that other processes such as dynamical friction and AGN feedback effects may contribute to the creation of cores in the inner regions of massive galaxies (e.g. A number of observations and black hole accretion models (e.g., Marconi et al 2004;Merloni 2004;Granato et al 2006;Lapi et al 2006;Zheng et al 2009;Silverman et al 2008;Shankar et al 2009b;Mullaney et al 2012;Lapi et al 2014) suggest some degree of correlation between black hole growth and large-scale star formation. On the other hand, a number of observational and theoretical studies are now showing that the actual coevolution may be more complex to probe observationally, possibly depending on the different evolutionary phases undergone by the host galaxies as well as AGN variability effects (e.g., Hickox et al 2014;Rodighiero et al 2015;Volonteri et al 2015;Graham 2016;Westhues et al 2016, and references therein).…”
Section: Implications For the Co-evolution Of Black Holes And Galaxiesmentioning
confidence: 99%